РУССКИЙ ВОКАЛИЗМ В ЗЕРКАЛЕ ЕВРОПЕЙСКИХ ЗВУКОВЫХ СИСТЕМ: ТИПОЛОГИЧЕСКОЕ И СПЕЦИФИЧЕСКОЕ - Логинова, Инесса (Studia Rossica Posnaniensia, 2008)
In this article the Russian vocalism is presented in accordance with the phonetic formation of the word sound structure of which is generally defined by the word stress and the hard-soft category of consonants. Some specific characters of the sound structure of the Russian word in the speech stream which were received after the comparative analysis of the Russian and some European vocalic systems are shown in the paper.